HUBUNGAN KETERATURAN PENGGUNAAN INHALER TERHADAP HASIL ASTHMA CONTROL TEST (ACT) PADA PENDERITA ASMA - Wahyudi Fadzila; Bayhakki Bayhakki; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Asthma is one of the non-communicable chronic diseases and often occur repeatedly if it is not being controlled. One of tools used to describe astma control quantitatively or semi quantitatively is Asthma Control Test (ACT). This research aimed to determine correlation between regularity of the use of inhaler and asthma control test result of asthma’s patients. This research used correlatioal method with cross sectional design. Sampling method was purposive sampling with 30 respondents. The instrument in this research was questionnaire to see regularity of the use of inhaler. The data analyses were univariate analysis and bivariate to determine relationship between two variables by using KolmogorovSmirnov test. Results found there is correlation between regularity of the use of inhaler with asthma control test on asthma’s patient with p value = (0,028) <ɑ (0,05). This research recomends to every public health center need to perform evaluation on regularity of the use of inhalers and check asthma control test periodically. Keywords : Asthma, Asthma Control Test (ACT), Inhalers